PENERAPAN STANDAR AKUNTANSI KEUANGAN SYARIAH PADA KOPERASI JASA KEUANGAN SYARIAH (STUDI PADA BAITUL QIRADH DI KOTA BANDA ACEH) - IKHSAN, AMRUL; Haridhi, Musfiari (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study is a descriptive study conducted on implementing SFAS (Statement of Financial Accounting Standard) Sharia to Baitul Qiradh in Banda Aceh. This study aims to know how the accounting practices regarding to financial statements presentation according to SFAS 101 towards the sharia financial statements presentation, the recognition, measurement, presentation and disclosure of murabaha transactions under SFAS 102 concerning murabaha and mudaraba accounting under PSAK 105 concerning mudaraba accounting applied to BaitulQiradh in Banda Aceh.The research method used is qualitative descriptive method. The object of this research is active BaitulQiradh in Banda Aceh. The data used in this study is the primary data sourced from Baitul Qiradh.The results shows that BaitulQiradh in Banda Aceh has not been able to apply accounting practices in accordance to Sharia SFAS. Therefore, BaitulQiradh management is expected to improve the human resources to be able to practicing accounting in accordance with Sharia SFAS 101, 102, and 105